Estrategia de desarrollo de Turismo Comunitario en el Corregimiento de Bonda del Distrito de Santa Marta para la catalización intercultural de las comunidades (2024)
The purpose of the following research is to analyze community-based tourism as an economic development alternative for the district of Bonda in the District of Santa Marta, taking advantage of the new consumption trends, preferences and experiences that tourists currently have. For the implementation of this proposal, it is intended to take advantage of the benefits offered by community tourism and rural tourism in a city with great historical, natural and cultural richness, with a great diversity of landscapes such as Santa Marta. This project is expected to promote the preservation of places as tourist attractions, thanks to the community participation that contributes to protect the environment in the communities where they live and develop their daily activities. It should be noted that the research presents a position framed in a mixed methodology, since it makes use of qualitative and quantitative aspects. For this purpose, different instruments are available for the collection of primary and secondary information with which it is intended to evidence and have knowledge on the subject of study and formulation in the aforementioned villages. Similarly, at the institutional level, the study is carried out in accordance with the guidelines of the field of organizational management research.